Effects of Harvest Method on Microclimate in Florida Sugarcane - Hardev Sandhu; Maninder Singh; Robert Gilbert; Kelly Morgan; Ronald Rice; Leslie Baucum; James Shine; Mike Irey (EDIS, 2015)
The production systems for sugarcane include either green cane or burnt cane harvesting operations. Sugarcane in Florida is typically harvested with burnt cane mechanical harvesting, but there is a growing interest to better understand the effects of green cane harvest residue “trash blankets” on microclimate conditions for sugarcane growing on both organic and mineral soils of Florida, so the authors conducted a three-year study to determine the effects of each harvest method on microclimate within the surface soil profile and at a 10 cm height from the soil surface. Results are presented in this 3-page fact sheet written by Hardev Sandhu, Maninder Singh, Robert Gilbert, Kelly Morgan, Ronald Rice, Leslie Baucum, James Shine Jr., and Mike Irey, and published by the UF Department of Agronomy, April 2015. (UF/IFAS Photo: Josh Wickham.)